2001
DOI: 10.1097/00000658-200107000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Halsted Revisited: Internal Mammary Sentinel Lymph Node Biopsy in Breast Cancer

Abstract: Internal mammary sentinel node biopsy is feasible without serious additional complications. It improves nodal staging in breast cancer by identifying higher-risk subgroups with internal mammary nodal metastases, which might benefit from altered adjuvant treatment regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
2
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(99 citation statements)
references
References 33 publications
6
86
2
5
Order By: Relevance
“…The SLNs in previous studies were found in the axilla, internal mammary, and supraclavicular nodes. But the frequency of extraaxillary SLNs including internal mammary nodes was slightly lower than in previous studies (10.76% vs. 17%-56% and 8.34% vs. 10%-40%, respectively) (32)(33)(34)(35).…”
Section: Discussioncontrasting
confidence: 59%
“…The SLNs in previous studies were found in the axilla, internal mammary, and supraclavicular nodes. But the frequency of extraaxillary SLNs including internal mammary nodes was slightly lower than in previous studies (10.76% vs. 17%-56% and 8.34% vs. 10%-40%, respectively) (32)(33)(34)(35).…”
Section: Discussioncontrasting
confidence: 59%
“…This was followed by IM-SLNB whenever lymphoscintigraphy highlighted IMC drainage. The IM-SLNB technique, based on the IM-SLNB method described by van der Ent [19] can usually be performed using the mastectomy incision. In breast conserving operations, a small additional horizontal incision (2.5-3 cm) over the desired interspace was used to sample IMSLNs.…”
Section: Dmentioning
confidence: 99%
“…Metastases exclusively situated in the IM node, without concurrent axillary metastases, occur in 2-11% of patients [85]. A larger axillary metastatic load may represent a higher risk of IMC metastasis [1], and the total number of involved nodes in the two regions together may likewise be important from a prognostic aspect, but this is currently very difficult to assess, as IMC-LND is not part of the standard treatment of breast carcinoma [22].…”
Section: Internal Mammary Sentinel Lymph Node Biopsy In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 14 cases, 10 had positive axillary nodes at the same time, confirming again that axillary node positivity in the case of drainage to IMN is a strong predictive factor for IMN metastasis. Van der Ent et al 36 investigated internal mammary chain metastasis in 256 patients. This paper reported IMN metastasis in 26.8% (11/41).…”
Section: Factors Associated With Imn Drainage and Metastasismentioning
confidence: 99%